2011
DOI: 10.3354/cr01010
|View full text |Cite
|
Sign up to set email alerts
|

Climate of the last millennium at the southern pole of the North Atlantic Oscillation: an inner-shelf sediment record of flooding and upwelling

Abstract: Continental and marine conditions during the last millennium off Porto, Portugal (the southern pole of the North Atlantic Oscillation, NAO), are reconstructed from a sediment archive through a high-resolution multiproxy study and instrumental evidence. Results show multidecadal variability and sea surface temperatures (SSTs) that correlate well with previously published landand sea-based Northern Hemisphere temperature records, and appear to be responding to long-term solar insolation variability. Precipitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 88 publications
(97 reference statements)
2
34
0
Order By: Relevance
“…The transition to the Industrial Era, in the northern Porto site, although distinct at 1850 CE, starts at 1730−1740 CE (Abrantes et al, 2011) and is accompanied by the return of SSTs to the values observed pre 1300 CE. A pattern that coincides with the atmospheric temperature rise detected in NE Spain, 25…”
Section: The Industrial Eramentioning
confidence: 99%
See 4 more Smart Citations
“…The transition to the Industrial Era, in the northern Porto site, although distinct at 1850 CE, starts at 1730−1740 CE (Abrantes et al, 2011) and is accompanied by the return of SSTs to the values observed pre 1300 CE. A pattern that coincides with the atmospheric temperature rise detected in NE Spain, 25…”
Section: The Industrial Eramentioning
confidence: 99%
“…The transition into the Industrial Era is also marked by a shift in the phytoplankton community and water column stratification over the northern Porto site, which was interpreted by Abrantes et al, (2011), as a response to a reduction in the summer and/or annual upwelling and more frequent fall−winter upwelling-like events, on the basis of published evidence ( (Abrantes et al, 2011;Alvarez et 35 Clim. Past Discuss., doi:10.5194/cp-2017-39, 2017 Manuscript under review for journal Clim.…”
Section: The Industrial Eramentioning
confidence: 99%
See 3 more Smart Citations